Motivasi dan Orientasi Masa Depan: Penentu dalam Pendidikan Calon Guru Agama - Siswantara, Yusuf; Satya Bhakti, Angga (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
This study delves into the motivation and future orientation of prospective religious teachers in Indonesia, exploring the factors that influence their decision to choose an educational path as spiritual educators. The focus of the research was to understand the factors that influenced their decision in choosing education as a religious teacher. Through a qualitative approach with the phenomenological interview method, data was obtained from respondents who revealed that their main motivation was the desire to make a positive impact on students' spiritual lives. Religious values such as love, service, and moral responsibility are the main drivers in choosing this profession. Personal experience related to religious practices and involvement in faith communities also contribute significantly to their motivation. The future picture of the respondents shows the aspiration to be educators with integrity and agents of change in the community. This research suggests the need to develop spiritually-based career programs for prospective religious teachers, which can assist them in their future roles as leaders and servants in the context of value-based education. These findings are expected to provide in-depth insights for the study of education and student character development in the context of religious education.